Rhetorical Situation and Academic Writing for the Master’s Program in English: A Review - Pandey, Hem Lal (SCHOLARS: Journal of Arts & Humanities, 2020)
This paper reflects on what writing practices are taking place in the M.A. English Curriculum in Tribhuvan University. Along with some theoretical discussions on the rhetorical situation and writing process, it observes and makes a review of firsthand experience of the teachers and students’ in classes of the Academic Writing course. Here, through this paper, my attempt is to bring three issues together: illustrate the objective of academic writing course implemented in the M. A. English Program; reflect on the students' real experience with it; and present some ways to help students overcome 'writer's block' while preparing different term papers and final thesis that they are required to write. Obviously, the targeted audience of my paper are the students; fellow colleagues (since I have collected genuine classroom experience of the students and my own and have presented them with a purpose) and the authorities of TU as well (because students who are required to write need support of the library, the online sources and publishing forums). As a faculty exposed in both the annual and semester systems, I have also highlighted some differences that I have observed and noticed between the goals of curriculum of annual and semester. The small size classroom, easy access to the online databases and opportunity to publish best papers, serious efforts and perseverance of the instructors and the students, regular seminars and workshops, and remedial classes on language and editing are some immediate exigencies for making students adept in academic writing. Only after meeting these requirements and the management of archival collection of students' writing to verify originality and plagiarism, we can really stimulate students' interest in writing and institutionalize the academic writing culture in the university..